Sucrose ingestion causes opioid analgesia - Segato,F.N. (1997)
The intake of saccharin solutions for relatively long periods of time causes analgesia in rats, as measured in the hot-plate test, an experimental procedure involving supraspinal components. In order to investigate the effects of sweet substance intake on pain modulation using a different model, male albino Wistar rats weighing 180-200 g received either tap water or sucrose solutions (250 g/l) for 1 day or 14 days as their only source of liquid. Each rat consumed an average of 15.6 g sucrose/day. Their tail withdrawal latencies in the tail-flick test (probably a spinal reflex) were measured immediately before and after this treatment. An analgesia index was calculated from the withdrawal latencies before and after treatment. The indexes (mean ± SEM, N = 12) for the groups receiving tap water for 1 day or 14 days, and sucrose solution for 1 day or 14 days were 0.09 ± 0.04, 0.10 ± 0.05, 0.15 ± 0.08 and 0.49 ± 0.07, respectively. One-way ANOVA indicated a significant difference (F(3,47) = 9.521, P<0.001) and the Tukey multiple comparison test (P<0.05) showed that the analgesia index of the 14-day sucrose-treated animals differed from all other groups. Naloxone-treated rats (N = 7) receiving sucrose exhibited an analgesia index of 0.20 ± 0.10 while rats receiving only sucrose (N = 7) had an index of 0.68 ± 0.11 (t = 0.254, 10 degrees of freedom, P<0.03). This result indicates that the analgesic effect of sucrose depends on the time during which the solution is consumed and extends the analgesic effects of sweet substance intake, such as saccharin, to a model other than the hot-plate test, with similar results. Endogenous opioids may be involved in the central regulation of the sweet substance-produced analgesia.